A sensitivity analysis of the stepwise measurement procedure for the characterization of large area PV modules. (April 2016) - Rapp, Christoph; Steiner, Marc; Siefer, Gerald; Bett, Andreas W.
Highlights: A procedure to characterize PV modules using smaller sun simulators was presented previously. Now, the sensitivity of this procedure concerning disturbing factors is investigated. A network model to simulate the I – V curves of different modules is presented. With that, we determined the impact of the disturbing factors. Using these outcomes, recommendations to gain highest accuracies are given. Abstract: A major issue in the characterization of photovoltaic modules is the limitation of the homogenously irradiated area provided by the available sun simulators. Therefore the S tepwise M easurement P rocedure for the Characterization of Large - area PV Modules ( SMP ) was developed recently. This concept enables the characterization of modules with aperture areas larger than the area provided by a given sun simulator. In previous investigations the procedure demonstrated good applicability and high accuracy. In a real application environment, however, conditions like temperature and stray light might influence the measurement. Also, particular variations within a module like e.g. defective cells may lead to higher uncertainties for the results of the SMP. Therefore, an investigation of the impact of these factors on the accuracy of the procedure is performed. The results show that the impact of most factors can be minimized and even eliminated. Therefore, recommendations for the practical application are given.